Perancangan Kursi Roda Terapi untuk Penderita Stroke - Kartika Suhada; Rainisa Maini Heryanto; Winda Halim; Tubagus Panji Ismail (OPSI, 2023)
Stroke could cause paralysis and reduced body function. In an effort to self-mobilize, a stroke patient needs a wheelchair. Even though the existing wheelchairs have undergone significant development, both in terms of design and technology, the function of these wheelchairs is still limited, to assist users in carrying out their daily activities and there is no wheelchair that functions as a wheelchair. therapy tool. One way to recover from a stroke and help prevent further disability is therapy, both medical therapy and alternative therapy. Therefore, in this study a wheelchair was designed to function as a therapeutic tool by making circular movements carried out by the arms, hands and legs as well as movements away from and towards the chest carried by the arms and hands so that the muscles could be strengthened, thus helping the recovery process from stroke, especially those that attack the hands and feet of stroke sufferers. The method used in the design is design thinking that focuses on humans, knowing user needs, and innovating according to user needs. The design thinking process consists of 5 stages: empathize, define, ideate, prototype, and test. In its design, wheelchairs are also made to consider ease of installation and use.